2019
DOI: 10.1016/j.heliyon.2019.e01826
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cervical cancer prevention education in middle-school girls in Korea: A mixed-method study

Abstract: Purpose The aim of this study was to determine the effects of cervical cancer prevention education (CCPE) among Korean middle-school girls in terms of whether it provided them with a positive perception of the Papanicolaou test (Pap test) and encouraged them to undergo Pap testing in adulthood. Methods A mixed-method design was used to only one group of 15 people, which combined a one-group pretest-posttest design with a qualitative study and a focus group interview (FG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…These findings were consistent with the previous study performed by Gottvall et al ( 45 ) where a school-based interventional study was able to improve HPV awareness through classroom teaching and website. Similarly, another study from Kim et al showed that cervical cancer prevention education was able to educate participants significantly regarding the essence of cervical cancer prevention ( 16 ). Our study results indicate an improvement in knowledge concerning cervical carcinoma, Pap smear test and HPV vaccine.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…These findings were consistent with the previous study performed by Gottvall et al ( 45 ) where a school-based interventional study was able to improve HPV awareness through classroom teaching and website. Similarly, another study from Kim et al showed that cervical cancer prevention education was able to educate participants significantly regarding the essence of cervical cancer prevention ( 16 ). Our study results indicate an improvement in knowledge concerning cervical carcinoma, Pap smear test and HPV vaccine.…”
Section: Discussionmentioning
confidence: 98%
“…Gottvall et al reported that educational intervention was unable to change participants' intention of getting a pap smear test and the usage of condom ( 45 ). Similarly, Kim et al also reported that educational intervention failed to improve the negative response of high school students toward being screened by pap smear test ( 16 ). However, the results of this study contradict the findings of Kim et al and Gottvall et al in that, participant's willingness of getting a pap smear test increased in our study after the intervention indicating a positive attitude toward getting a pap smear test.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to health education, the target of saving money is to alleviate vaccination financing. Kim et al, (2019) found that most respondents receiving cervical cancer prevention education had significant improvement in adolescents' cervical cancer understanding. Chinwe et al, (2015) also found that their respondents had relatively good knowledge of cervical cancer and cervical cancer screening after receiving health education.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, a free HPV vaccination program for young girls aged 12 was introduced in 2016. Moreover, health education is effective in creating awareness for and improving the knowledge of reproductive-aged women about cervical cancer and prevention, particularly in younger girls [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%